Corruption in Nepal: Level, Pattern and Trend Analysis - Gupta, Anil Kumar; Adhikari, Shiva Hari; Shrestha, Gyan Laxmi (Journal of Management and Development Studies, 2018)
The Government of Nepal has adopted various policies, plans and programs to curb corruption over the years. However, Transparency International (2015) showed that there is a high level of corruption in Nepal. Bearing such aspect in the mind, the study aims to analyse level, pattern and trend of corruption in Nepal by analysing the cases published by Commission for the Investigation of Abuse of Authority in its annual reports from 2005 to 2015. Applying descriptive and bivariate analysis, it draws a level, trend and pattern of corruption and improper conduct using the disaggregated level data. Similarly, it seeks to analyse the relationship between corruption and gender as well as a position of a public official and working place of officials. Findings of this study showed that Nepal has relatively decreased the global corruption index of 2015 compared to 2013 and 2014. It is interesting to note that corruption cases lodged decreased dramatically from 2006 to 2008, however, it started to increase from 2008 onward. Similarly, it is seen that there was no significant fluctuation noticed in the number of complaints received and resolved in the Year between 2006 and 2015. During the Year between 2005 and 2015, the Central Development Region had the highest annual number of corruption and improper complaints registered, whereas the Far-Western Development Region had the lowest. Similarly, Tarai districts recorded the highest number of corruption cases complaints between 2005 and 2013. During the Year 2005 to 2015, Mahottari was repeatedly listed in the top 10 districts registering highest number of corruption and improper conduct's complaints. Additionally, this study also showed a significant relationship in gender, position, working place, and types of corruption with small to moderate effect which offers a new and conclusive perspective in a debate in the scientific community regarding their association.